2020
DOI: 10.1101/2020.03.13.20035428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological immunochromatographic approach in diagnosis with SARS-CoV-2 infected COVID-19 patients

Abstract: An outbreak of new coronavirus SARS-CoV-2 was occurred in Wuhan, China and rapidly spread to other cities and nations. The standard diagnostic approach that widely adopted in the clinic is nuclear acid detection by real-time RT-PCR. However, the false-negative rate of the technique is unneglectable and serological methods are urgently warranted. Here, we presented the colloidal gold-based immunochromatographic (ICG) strip targeting viral IgM or IgG antibody and compared it with real-time RT-PCR. The sensitivit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 17 publications
(21 reference statements)
4
111
0
7
Order By: Relevance
“…The diagnostic indexes of LFIA-based IgM/IgG tests were demonstrated at different time points after onset of the symptoms, wherein at 0-7 days, 8-15 days and 16 days or more after symptom onset these tests showed 18.8%, 100% and 100% sensitivity and 77.8%, 50% and 64.3% specificity, respectively. 13 A similar study by Pan et al 46 with RT-PCR-confirmed cases showed increase in sensitivity from 11.1% to 96.8% in LFIA within the first week and after 2 weeks of disease onset, respectively. However, in RT-PCR-negative suspected cases, the detection capacity by LFIA was 43.6%.…”
Section: Rapid Point-of-care Test In Sars-cov-2 Infectionmentioning
confidence: 77%
“…The diagnostic indexes of LFIA-based IgM/IgG tests were demonstrated at different time points after onset of the symptoms, wherein at 0-7 days, 8-15 days and 16 days or more after symptom onset these tests showed 18.8%, 100% and 100% sensitivity and 77.8%, 50% and 64.3% specificity, respectively. 13 A similar study by Pan et al 46 with RT-PCR-confirmed cases showed increase in sensitivity from 11.1% to 96.8% in LFIA within the first week and after 2 weeks of disease onset, respectively. However, in RT-PCR-negative suspected cases, the detection capacity by LFIA was 43.6%.…”
Section: Rapid Point-of-care Test In Sars-cov-2 Infectionmentioning
confidence: 77%
“…It has already been shown that a higher degree of sensitivity for detection of SARS-CoV-2 infections is reached through a combination of PCR and antibody tests. [1][2][3] Thereby, the sensitivity of PCR alone was higher at the early phase of disease, whereas antibody tests alone were more favorable at later time points.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The antibody response to SARS-CoV-2 infection seems to evolve after the onset of clinical symptoms 2,6 and after the beginning of virus replication and shedding. 7 The "classical view" on IgM responses preceding IgG responses has been encouraged by one of the first publications on SARS-CoV-2 serology, in which five of seven cases of acute infections with SARS-CoV-2 were serologically tested, using recombinant nucleoprotein and the enzyme-linked immunosorbent assay (ELISA) technique.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…. The LFIA test for COVID-19 detection takes 15 to 20 min, and has 90% sensitivity and specificity as reported by Li et al and Pan et al when tested on 400 patients' samples(Table 1)[21,22].…”
mentioning
confidence: 59%